Analisis Efektivitas Penerapan Sistem Pengendalian Internal Pada Manajemen Sarana dan Prasarana Di MTsS Al-Abror Muara Soma - Hasibuan, Nisa Sri Rahayu; Nurbaiti, Nurbaiti; Syafina, Laylan (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2023)
This study aims to determine the effectiveness of implementing the internal control system in the management of facilities and infrastructure at MTsS Al- Abror Muara Soma. This research was conducted at MTsS Al- Abror Muara Soma. This study uses qualitative research methods with a descriptive approach. Data collection techniques through observation techniques, interviews, and documentation. The research results show that the implementation of the internal control system in the management of facilities and infrastructure at MTsS Al- Abror Muara Soma is less effective. Can be seen by using the checklist method, the result of the calculation are 40% which means it is less effective in implementing the internal control system and 60% the effectiveness cannot be proven for environmental aspects of control, there is no segregation of duties in the coordinator of facilities and infrastructure, namely the existence of multiple positions carried out by the administration, and there is still a lack of concern in maintaining facilities and there are still incomplete and inadequate facilities. For the information and communication aspect, it is proven that the numbering of facilities has not been implemented, manual recording of inventory for each class has not been implemented and there is no recording system for removing facilities and infrastructure that are not longer used or left in stroge, and for the supervision aspect it has not been carried out properly because special staff have not been formed to supervise facilities and infrastructure and have not carried out routine inspections of school facilities.